Construction of biology magazine based on the antidiabetic test of pasak bumi roots - Michelle Terrence; Ruqiah Ganda Putri Panjaitan; Afandi Afandi (JPBIO (Jurnal Pendidikan Biologi), 2022)
The enrichment program is an additional effort or activity given to students who have achieved complete learning with the aim of increasing students' understanding and insight into the material being or has been studied. In carrying out the enrichment program, teachers can use enrichment materials as learning resources, one of which is a biology magazine. This study aims to develop a biology magazine as an enrichment material to increase students' understanding and insight into the hormone system sub-material. This type of research is an R&D research that uses an adaptation of the 4D Thiagarajan model, namely define, design, and development. The data sources for this research consisted of 36 students from Christian High School Immanuel Pontianak and SMA Santo Fransiskus Asisi Pontianak, 3 biology teachers from these schools, and 3 lecturers of Biology Education FKIP UNTAN. The results of the analysis of student needs indicate that it is necessary to develop a biology magazine in order to motivate students to increase their understanding and insight. The results of the feasibility test can be seen that biological magazines are suitable for use as material for enrichment of the hormone system sub-material, this is indicated by the Aiken's V value obtained 0.79.